Complications of invasive mycoses in organ transplant recipients. Issue 12 (1st December 2016) - Samanta, Palash; Singh, Nina
ABSTRACT: Introduction: Opportunistic mycoses remain a significant complication in organ recipients. Areas covered: This review is an evidence-based presentation of current state-of-knowledge and our perspective on recent developments in the field Expert commentary: Invasive fungal infections are associated with reduced allograft and patient survival, increase in healthcare resource utilization, and newly appreciated but largely unrecognized immunologic sequelae, such as immune reconstitution syndrome. Given adverse outcomes associated with established infections, prophylaxis is a widely used strategy for the prevention of these infections. Currently available biomarkers that detect circulating fungal cell wall constituents i.e., galactomannan and 1, 3-β-D-glucan have not proven to be beneficial as screening tools for employing targeted prophylaxis or as diagnostic assays in this patient population. However, subsets of patients at risk for opportunistic fungal infections can be identified based on clinically identifiable characteristics or events. Preventive strategies targeted towards these patients are a rational approach for optimizing outcomes.